Propuesta para la revitalización del centro histórico de Riobamba en el marco de Ciudad Universitaria - Inca Guerrero, Jeymi Madelen (2024)
Riobamba is one of the three cities declared as "university cities" in the country, despite this it is evident the lack of elements that classify as an efficient city of this category. On the other hand, we have the historic downtown of Riobamba, which despite its problems emerges as this potential element to house and complement those facilities and elements that a university city requires, this being the most important cultural, social, and commercial engine of the city and that at the same time could benefit from the presence of these institutions. This research seeks to generate an urbanarchitectural proposal that allows the revitalization of the historic center of Riobamba, considering those problems that this presents. To this end, it was sought to understand the historic center through a multi-scale analysis that in turn will allow us to identify the different potential points to intervene in an urban recovery plan that proposes the insertion of educational and cultural uses in the historic center as catalysts that allow the regeneration of those ruptures present in it and that, added to other strategies, allow the revitalization of it. All this converges in an architectural proposal that states the revaluation of a heritage property in abandonment, as it is the “Casa Vélez” understanding the abandonment and loss of architectural heritage assets as one of the great problems of the historic center of the city and the revaluation of heritage not as something independent of its environment but taking into account the insertion of the patrimonial good in the uses collectives for the city